American Economic Journal: Microeconomics - American Economic Association (Pittsburgh, PA American Economic Association, 2010)
American Economic Journal: Microeconomics publishes papers focusing on microeconomic theory; industrial organization; and the microeconomic aspects of international trade, political economy, and finance. The journal publishes theoretical work as well as both empirical and experimental work with a theoretical framework.
American Economic Journal: Microeconomics is published quarterly February, May, August and November.
Keywords: Microeconomics; MICROECONOMICS